2005
DOI: 10.1167/iovs.04-0089
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Its Association with Cataract: Results of the Andhra Pradesh Eye Disease Study from India

Abstract: Consistent with other studies, tobacco smoking was strongly associated with a higher prevalence of nuclear and cortical cataracts and history of prior cataract surgery in this population. These findings suggest yet another need to educate the community on the importance of cessation of tobacco smoking and perhaps incorporating an antismoking message into school health programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 49 publications
9
58
0
3
Order By: Relevance
“…The prevalence of cataracts was higher in women (42.3%) than in men (38.9%), which is in line with previous studies, 11,12,19 and could be explained by the difference in environmental exposure, and the results of hormonal changes associated with menopause. 20 Moreover, we found that the association between low SES and the high proportion of cataracts was observed only in women.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The prevalence of cataracts was higher in women (42.3%) than in men (38.9%), which is in line with previous studies, 11,12,19 and could be explained by the difference in environmental exposure, and the results of hormonal changes associated with menopause. 20 Moreover, we found that the association between low SES and the high proportion of cataracts was observed only in women.…”
Section: Discussionsupporting
confidence: 91%
“…8,14 Income or education levels were inversely related to the 10-year cumulative incidence of nuclear cataracts in the Beaver Dam Eye Study. 7 Similar trends were also observed in studies performed in Asian countries such as Singapore, 11,15 India, 12 China, 10 and Bangladesh. 16 The reason for the association between low SES and the prevalence of cataracts is yet to be elucidated, although several possible explanations have been suggested.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations